Some Gastrointestinal Tract Characteristics of Karayaka Ram Lambs Slaughtered at Different Weights - Arda Yıldırım; Yüksel Aksoy; Nuh Ocak; Zafer Ulutaş (The Scientific World Journal)
Thirty-one Karayaka ram lambs were slaughtered at different body weights (30 n=7, 35 n=6, 40 n=7, 45 n=6, and 50 n=5 kg of body weight at fast) to evaluate the growth of their gastrointestinal tract (GIT) characteristics, to determine the relationship among slaughter body weight (SBW) and empty body weight (EBW), whole GIT and segments, and the influence of slaughter weight on the pH of rumen, jejunum, and cecal contents. The effects of the SBW on GIT weight P<0.05, stomach P<0.001, and intestine P<0.05, the body length P<0.001 and caecum P<0.05, and the relative weights of GIT P<0.05, stomach P<0.001, and intestine P<0.001 were linear whereas that for the length of intestine were quadratic. The effect of SBW were quadratic P<0.05 on ratios of stomach to GIT weight and intestine length to intestine weight and rumen pH while, for the intestine to GIT weight ratio P<0.001 and caecum pH P<0.05, this effect was linear. The results indicated that for all parameters studied, with the exception of intestinal length and cecal pH, linear relationships were observed with SBW indicating steady growth rates for these tissues.